2010
DOI: 10.1186/1471-2202-11-23
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein-E forms dimers in human frontal cortex and hippocampus

Abstract: BackgroundApolipoprotein-E (apoE) plays important roles in neurobiology and the apoE4 isoform increases risk for Alzheimer's disease (AD). ApoE3 and apoE2 are known to form disulphide-linked dimers in plasma and cerebrospinal fluid whereas apoE4 cannot form these dimers as it lacks a cysteine residue. Previous in vitro research indicates dimerisation of apoE3 has a significant impact on its functions related to cholesterol homeostasis and amyloid-beta peptide degradation. The possible occurrence of apoE dimers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…These conformational differences have been confirmed through FRET assays in vitro (9,10). Biochemical analyses of human cerebrospinal fluid and blood-and brain-derived apoE have indicated the presence of apoE intermolecular interactions and have shown that E4 does not form covalently linked multimers, in contrast to E2 and E3 (11)(12)(13). Finally, two models have been suggested for the structure of secreted apoE lipoparticles in which apoE could either surround lipids in a belt-like formation with one apoE molecule per particle or bind to lipids in a 2:1 ratio with the two apoE molecules forming a 42 o angle (7, 14 -16).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…These conformational differences have been confirmed through FRET assays in vitro (9,10). Biochemical analyses of human cerebrospinal fluid and blood-and brain-derived apoE have indicated the presence of apoE intermolecular interactions and have shown that E4 does not form covalently linked multimers, in contrast to E2 and E3 (11)(12)(13). Finally, two models have been suggested for the structure of secreted apoE lipoparticles in which apoE could either surround lipids in a belt-like formation with one apoE molecule per particle or bind to lipids in a 2:1 ratio with the two apoE molecules forming a 42 o angle (7, 14 -16).…”
mentioning
confidence: 75%
“…These data suggest that E4 molecules are either at closer proximity to each other or that several E4 molecules come together to form larger complexes in comparison to E2 and E3. Previous biochemical findings have suggested that apoE forms large complexes without isoform-specific differences (13) but that E4 is unable to form disulfide bonds (11), suggesting that interactions between E4 molecules follow a different mechanism. In addition, for secreted apoE in our conditions, our data support the model according to which two apoE molecules surround a lipoparticle (7,14); if the alternative single molecule model (15,16) was true, there would be no intermolecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Using multiple approaches, we found that apoE4 binds to IR with higher affinity compared with apoE3; thus, apoE4 may block insulin-IR binding more efficiently. ApoE4 has been suggested to self-aggregate more easily than other apoE isoforms (Hatters et al, 2006), although there are some discrepancies regarding to the dimerization of apoE (Aleshkov et al, 1997; Elliott et al, 2010; Martel et al, 1997; Weisgraber and Shinto, 1991). It is also possible that the aggregated apoE4 physically interferes with the interaction between IR and insulin.…”
Section: Discussionmentioning
confidence: 99%
“…There is a presumed protective role of ApoE ε2 and ε3 in Pb53 and Hg54 toxicity for adults. When compared to ε4, these two genotypes are more frequent in a population, proteins are expressed more, have more Cys, and are capable of forming dimers55-57. Interestingly, in children, it is ApoE ε4 that protects them better than ApoE ε2 or ApoE ε3; among 311 subjects, the negative effects for umbilical cord Pb level on the Mental Development Index of the Baley Scale was almost 4-fold greater among ApoE ε2/3 carriers58.…”
Section: Resultsmentioning
confidence: 96%